Implementasi Permendikbudristek Nomor 30 Tahun 2021 Di Daerah Cikarang - Septiayu Restu Wulandari; Hasmi Kun Hidayah; Indah Wulansari (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2022)
Sexual violence is not a new thing, it is even increasing in the college environment as a place to get knowledge. Universities as higher education hold an important role in preventing and handling sexual violence in the that environment in order to create a humanist, dignified, equal, inclusive, collaborative, and non-violent condition. All aspects of the academic civitas must go on together in implementing Permenristekdiksti Number 30/2021. So that there will be no more sexual violence that leads to Victim Blamming.